SISTEM PENYALIRAN TAMBANG UNTUK MENGATASI GENANGAN AIR LIMPASAN DI FRONT PENAMBANGAN BLOK TIMUR PT. PRIMA DELIN AGRO PERMAI KABUPATEN SAROLANGUN PROVINSI JAMBI - Yelli Fitri; Murad Murad (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. The mining system of PT. Prima Delin Agro Permai applies an open pit system. The open mining system it is really affected by the weather, of the reasons is when it’s raining. Mining that applies an open pit system required to have a good pit drainage plan to prevent the puddle on the mining front so it can be interfere with the mining process. The purpose of this research to analyze the pump needs, and design the dimension of sump and the open channels. The recommendations they are 1 recommendation. Recommended to add 1 unit pump become 6 units pumps by fixing one unit that has broken. Recommendation number 2, the diversion channel that can minimized the runoff with the slop on the bottom channel (S) = 0, 30%, width of the channel (b) = 0, 5 m, the height of the channel (H) = 0,625 m and the cross sectional area (A) =0,375 m². The third (III) recommendation, the dimension of sump which the optimal one to accommodate the total water discharge, with a maximum volume on 21, 512 m³, the plan based on the needs to get the dimension of the sump with the length of the surface of the wells and the width of the surface of 69 m. The length of the bottom and the width of the bottom of the well is 62 m with a depth of 5 m.Keywords: Mine drain system, Mining front, Pumps, Open channels, Sump